Effective Communication in Academia: It Goes Both ways! - Domenick J Pinto (Academic Chairpersons Conference Proceedings, 2019)
This workshops explores both the positive and negative aspects of communication with faculty, staff and administration. It emphasizes the effectiveness of GOOD communication skills as well as the dangers of MISCOMMUNICATION. Case studies, audience participation, and excerpts from literature on the topic will be presented.
Keywords: peers; leadership; administration; communication; faculty